Kant on freedom, law, and happiness - Guyer, Paul, 1948- (Cambridge, U.K. ; New York : Cambridge University Press, 2000)
"The twelve essays in this collection argue for a radically different account of Kant's ethics. They explore an interpretation of his moral philosophy according to which freedom is the fundamental end of human action, but an end that can only be preserved and promoted by adherence to moral law. Moreover, Paul Guyer shows that while Kant did not view moral laws as simply prudential rules for the maximization of human happiness, he did hold that an interpersonal system of happiness should result from the free choices of individual human beings if made with due respect for the freedom of all other humans to choose their own ends and ways of life as well."--Jacket
Mendelssohn and Kant: one source of the critical philosophy -- The unity of reason: pure reason as practical reason in Kant's early conception of the transcendental dialectic -- Freedom as the inner value of the world -- Kant's morality of law and morality of freedom -- The possibility of the categorical imperative -- The strategy of Kant's Groundwork -- Kantian foundations for liberalism -- Life, liberty, and property: Rawls and Kant -- Moral worth, virtue, and merit -- From a practical point of view: Kant's conception of a postulate of pure practical reason -- Nature, freedom, and happiness: the third proposition of Kant's Idea for a universal history -- Nature, morality, and the possibility of peace
Includes bibliographical references and index
Keywords: Kant, Immanuel, -- 1724-1804; Ethics; Ethics